On three new species of non-marine ostracods (Crustacea: Ostracoda) from Northeast Thailand - Savatenalinton, Sukonthip (Zootaxa, 2015)
Three new species of non-marine ostracods, Strandesia martensi n. sp., Strandesia pholpunthini n. sp. and Oncocypris rostrata n. sp., are here described from the Northeastern part of Thailand. Strandesia martensi n. sp. is similar to Strandesia perakensis Victor & Fernando, 1981 and to Strandesia sanoamuangae Savatenalinton & Martens, 2010. It can be distinguished from these two species by the presence of a large dorsal hump on both valves, large anterior overlapping, the general shape of valve, the ornamentation of valve surface and the markedly long proximal seta of caudal ramus. The main distinguishing characters of Strandesia pholpunthini n. sp. are the compression on the right valve at the posterior extremity and the fact that left valve overlaps right valve anteriorly, while right valve overlaps left valve posteriorly. This results in unequal anterior and posterior extremities, which can be seen clearly in the dorsal view. Oncocypris rostrata n. sp. is the first record of this genus in Thailand. It obviously differs from others in the beak-like anterior extremity in dorsal view, the valve structure in interior view, the valve ornamentation comprising of large pustules and large pits and the                 morphology of male reproductive organ, especially the first segment of the right prehensile-palp bearing a long apical spine and a large protrusion on the distal margin toward the second segment. A note on morphology, chorology and a key to the species of Oncocypris are given.